Structural and non-coding variants increase the diagnostic yield of clinical whole genome sequencing for rare diseases - Pagnamenta, AT; Camps, C; Giacopuzzi, E; Taylor, JM; Hashim, M; Calpena, E; Kaisaki, PJ; Hashimoto, A; Yu, J; Sanders, E; Schwessinger, R; Hughes, JR; et al. (BioMed Central, 2023)
Background Whole genome sequencing is increasingly being used for the diagnosis of patients with rare diseases. However, the diagnostic yields of many studies, particularly those conducted in a healthcare setting, are often disappointingly low, at 25–30%. This is in part because although entire genomes are sequenced, analysis is often confined to in silico gene panels or coding regions of the genome.